Nanosensors : Theory and Applications in Industry, Healthcare and Defense - Lim, Teik-Cheng. (Boca Raton : CRC Press, 2011)
Nanosensors, sensing devices with at least one sensing dimension less than 100nm, have become instrumental for monitoring physical and chemical phenomena, detecting biochemicals in cellular organelles, and measuring nanoscopic particles in industrial processes. This book provides a guide to nanosensors. Inspired by his own experience with nanofiber-based gas sensors, the author explains the principles and applications of nanosensors for industry, healthcare, and defense. Each chapter presents an overview of the specific type of nanosensor and then describes the fundamental science that forms the basis of the sensing mechanism, fabrication techniques, and the specific nanosensor's detection--
1. Carbon-nanotube-based sensors / Lianxi Zheng and B.C. Satishkumar -- 2. Carbon-nanotube-based fluidic shear-stress sensors / Winnie W.Y. Chow, Yanli Qu, and Wen J. Li -- 3. Nanomechanical cantilever sensors : theory and applications / Yifan Liu, Wenxing Wang, and Wenmiao Shu -- 4. Protein thin films : sensing elements for sensors / Laura Pastorino and Svetlana Erokhina -- 5. FRET-based nanosensors for intracellular glucose monitoring / Jithesh V. Veetil, Sha Jin, and Kaiming Ye -- 6. Noble metal nanoparticles as colorimetric probes for biological analysis / Xiaodi Su -- 7. Optical capillary sensors for intelligent classification of microfluidic samples / Michal Borecki and Michael L. Korwin-Pawlowski -- 8. Future healthcare : bioinformatics, nano-sensors, and emerging innovations / Shoumen Palit Austin Datta.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Nanotechnology; Detectors; Nanoelectromechanical systems; Electronic books